Risk Factors for Sigmoid Colonic Anastomosis: A Comparative and Cross-Sectional Analysis - Talih T; Sonmez G; Sozuer EM; Tombul ST; Kulturoglu MO; Islam DG; Akyıldız HY; Demirtas A; Karaagac M; Dal F (Therapeutics and Clinical Risk Management)
Tutkun Talih,1 Gokhan Sonmez,2 Erdogan M Sozuer,1 Sevket Tolga Tombul,3 Mahmut O Kulturoglu,4 Dogan G Islam,1 Hızır Y Akyıldız,1 Abdullah Demirtas,2 Mustafa Karaagac,1 Fatih Dal1 1Department of General Surgery, Erciyes University, Kayseri, Turkey; 2Department of Urology, Erciyes University, Kayseri, Turkey; 3Department of Urology, Acibadem Hospital, Kayseri, Turkey; 4Department of General Surgery, Etlik City Hospital, Ankara, TurkeyCorrespondence: Gokhan Sonmez, Email gokhans72@hotmail.comObjective: To evaluate the anastomotic leakage (AL) rates in cancerous and non-cancerous intestinal anastomoses and analyze the general risk factors for AL.Methods: The primary endpoint of this study is to investigate whether there is a difference in terms of AL between patients who underwent sigmoid colon resection + colorectal anastomosis due to primary colon cancer (Group 1) and patients with a completely healthy colorectal region who underwent sigmoid colon resection + colorectal anastomosis for use in the orthotopic bladder during radical cystoprostatectomy (Group 2). The secondary endpoint, considering all the patients, is to evaluate and investigate the risk factors affecting the AL rates.Results: A total of 178 patients, including 63 (35.4%) patients in Group 1 and 115 (64.6%) patients in Group 2, were included in the study. The mean age of all patients was 61.7 ± 9.9 years, and there was no statistical difference between the mean ages of the groups (62.8 ± 11.3 vs 60.7 ± 6.1, p = 0.106, respectively). Thirty-six (20.2%) of the patients were female, and 142 (79.8%) were male. There was no significant difference between the groups in terms of AL in the postoperative period. Postoperative AL was seen in three patients (4.8%) and six patients (5.2%) in Group 1 and Group 2, respectively (p = 0.642). According to univariate and multiple logistic regression analysis, the risk of AL increased in patients with comorbidities, in the presence of previous abdominal surgery, in patients with high neutrophil-to-lymphocyte ratio, and patients with postoperative ileus (p values are 0.042, 0.010, 0.029 and 0.048, respectively).Conclusion: Our data suggest that anastomosis due to colon cancer resection does not increase the risk of AL compared with healthy bowel anastomoses. In addition, some clinical factors have been found to compromise anastomotic safety and are risk factors for AL. In addition, some clinical factors have been found to endanger anastomotic safety and are risk factors for AL.Keywords: colorectal anastomosis, anastomotic leakage, bladder cancer, colon cancer, risk factors